Meningkatkan Kemampuan Berpikir Kritis Dan Motivasi Belajar Menggunakan Model Pembelajaran Lentera Pada Pembelajaran IPS Kelas V SDN Kebun Bunga 6 Banjarmasin - Nisrina Qurratu’ Ain; Ahmad Suriansyah (CV. ITTC INDONESIA, 2024)
The problem in this research is the low level of critical thinking skills and students' learning motivation in social studies learning. The reason is because learning is only one way, so students cannot think critically in solving problems, teachers do not use varied models so students find it difficult to understand social studies learning concepts, students are not able to realize learning in everyday life so student learning outcomes do not meet KKM standards. An effort to overcome this problem is by applying the LENTERA model in learning. This research used Classroom Action Research (PTK) which was carried out at four meetings. The research subjects were 19 class V students at SDN Kebun Bunga 6 Banjarmasin in the second semester of the 2023/2024 academic year. Qualitative data was obtained through observing teacher activities, student activities, critical thinking skills and student learning motivation using observation sheets. Quantitative data is the acquisition of student learning outcomes through group and individual written test assessments. Data analysis in this research uses descriptive cross-tabulation analysis, explained with tables, graphs and interpretation with percentages. The results of this research show that teacher activity at meetings I to IV increased from a score of 33 to a score of 46. Student activity at meetings I to IV increased from a percentage of 47% to 89% with very active criteria. Students' critical thinking skills at meetings I to IV increased from 57% to 89% with very skilled criteria. Student learning motivation at meetings I to IV increased from a percentage of 33% to 95% with very high criteria. Completeness of student learning outcomes increased from a percentage of 42% to 100%. Based on the results of this research, it can be concluded that the use of the LENTERA model can improve the quality of teacher activities, student activities, critical thinking skills, student learning motivation and student learning outcomes. It is recommended that this research can be used as an alternative in improving critical thinking skills, student learning motivation and results. Study